Peningkatan Mutu Pusat Pembelajaran Sunan Kalijogo dengan Strategi Two Stay Two Stray - Tri Esti Rahayuningtyas; Widyatmoko Widyatmoko; Mahadika Pradipta Himawan; Choerul Umam (SAP (Susunan Artikel Pendidikan), 2025)
The learning system in non-formal educational institutions still faces challenges such as low active student participation and the dominance of a tutor-centered approach that makes the learning process monotonous. Therefore, innovative, interactive, and student-centered learning strategies are needed to create an interesting and meaningful learning atmosphere. This study aims to evaluate the effectiveness of the Two Stay Two Stray (TSTS) learning strategy in improving the quality of education at the Sunan Kalijogo Kediri Community Learning Center (PKBM) and provide strategic recommendations for innovative student-centered learning. The study was conducted in May 2025 using a qualitative approach, focusing on the experiences, behaviors, motivations, and interactions of participants holistically. The TSTS strategy fosters active two-way communication between tutors and students. So that students can express opinions, share ideas, and collaborate in finding solutions to help reduce boredom and improve understanding. The findings show that TSTS increases student participation and encourages a more interesting, inclusive, and humanistic learning environment, thereby improving the quality of teaching. The study contributes academically by becoming the basis for further research on the TSTS method in other PKBM programs, such as skills or entrepreneurship training.